Perkembangan Emosional Remaja Yatim Piatu - Kalis Stevanus; Maria Setiarini (Pascasarjana IAKN Manado, 2022)
It is undeniable that the death of biological parents can affect the emotional development of children. The purpose of this study is to reveal the reality of the emotional development of orphaned adolescents at the Dorkas Sidoarjo Orphanage. To answer the purpose of the author uses a literature study research method in a phenomenological perspective. The findings of this study there are two factors that influence the emotional development of adolescents. The internal factor is the age when teenagers face the death of one or both of their parents, which greatly affects their emotional development: feelings of worthlessness, anxiety and depression arise and some even fall into juvenile delinquency who deal with the police. The external factor is spiritual development and is also supported by a conducive atmosphere full of kinship in the orphanage which has a positive impact on emotional development.